Does Admission to Hospital Affect Trends in Survival and Dependency After Stroke Using the South London Stroke Register?. Issue 9 (September 2016) - Bhalla, Ajay; Wang, Yanzhong; Rudd, Anthony; Wolfe, Charles D.A.
Abstract : Background and Purpose—: Despite guidelines for specialist assessment in hospital for stroke, it is important to identify patient characteristics, trends, and outcome in patients not admitted to hospital compared with patients admitted to hospital. Methods—: Population-based stroke register of first in a life time strokes between 1995 and 2012 were examined. Baseline data included admission or nonadmission, case mix, stroke subtype, and risk factors before stroke. Survival curves were estimated with Kaplan–Meier methods. Logistic regression was used to determine factors associated with poor outcome (dead and dependency: Barthel index, <15) at 3 months and 1 year. Results—: Three thousand four hundred sixty-four patients were admitted to hospital for stroke. Patients admitted were more likely have more severe impairments ( P <0.001). There was a significant trend for increasing admission over time; 1995 to 2000 (82%), 2001 to 2006 (90%), and 2007 to 2012 (94%); P <0.001. When survival analysis was stratified according to Barthel index ≥15 at day 7, there were no significant differences in survival curves between admission and nonadmission groups in 1995 to 2000 ( P =0.15) or 2001 to 2006 ( P =0.06), but there was a significant trend for higher survival rates for nonadmission in the 2007 to 2012 cohort ( P =0.025). Admission to hospital (stroke unit) compared with nonadmission was also associated with poor outcome in the 2001 to 2006 time period (odds ratio, 2.66; confidence interval, 1.17–6.04) and the 2007 to 2012 time period (odds ratio, 5.26; confidence interval, 1.27–21.81). Conclusion—: There is a survival advantage from 2007 onward and lower levels of dependency from 2001 onward after adjusting for case mix for those patients who are not admitted to hospital, which requires further explanation. Abstract : Supplemental Digital Content is available in the text.